COOPERATIVE LEARNING STAD TYPE METHOD TO IMPROVE THE STUDENTS READING ACHIEVEMENT - Amin, Bahrun (EXPOSURE JOURNAL, 2012)
ABSTRACTThe objective of the research is to find out the improvement of the studentsâ reading achievement. It is done through cooperative learning STAD type method. It is a classroom action research at the first grade students of SMP Kartika XX-3 Makassar. The research was conducted in two cycles in which every cycle consisted of four meetings. This research was held at the first year students of SMP KARTIKA XX-3 MAKASSAR. Subject in this research was class VII.B in 2011/2012 academic year. The studentsâ improvement in reading comprehension could be seen in their mean score namely 5,59 in D-test, 6,33 in cycle 1 and then it became 7,29 in cycle 11. The studentsâ literal reading comprehension dealing with the main idea and meaning of the word sentence in reading text was 5, 65 in D-test 6, 44 in cycle 1 and it became 7, 65 in cycle 11. In D-test in first meeting the percentage of studentsâ activeness is 69%, and in second meeting is 75%, and in third meeting is 77% while in the last meeting is 82%. And then after the evaluation in the cycle II the improvement of the studentsâ reading comprehension. Key Word: Reading, STAD type.Tujuan dari penelitian ini adalah untuk mengetahui peningkatan prestasi membaca siswa. Hal ini dilakukan melalui pembelajaran metode kooperatif tipe STAD. Ini adalah penelitian tindakan kelas pada siswa kelas pertama SMP Kartika XX-3 Makassar. Penelitian ini dilakukan dalam dua siklus dimana setiap siklus terdiri dari empat pertemuan. Penelitian ini dilakukan pada siswa tahun pertama SMP KARTIKA XX-3 MAKASSAR. Subjek dalam penelitian ini adalah kelas VII.B di tahun akademik 2011/2012. Siswa peningkatan pemahaman bacaan dapat dilihat pada nilai rata-rata mereka yaitu 5,59 di D-tes, 6,33 pada siklus 1 dan kemudian menjadi 7,29 pada siklus 11. siswa pemahaman membaca literal berkaitan dengan ide utama dan makna kalimat kata dalam membaca teks adalah 5, 65 di D-test 6, 44 dalam siklus 1 dan itu menjadi 7, 65 dalam siklus 11. D-tes di pertemuan pertama persentase keaktifan siswa adalah 69% , dan di pertemuan kedua adalah 75%, dan dalam pertemuan ketiga adalah 77% sedangkan pada pertemuan terakhir adalah 82%. Dan kemudian setelah evaluasi dalam siklus II peningkatan membaca pemahaman siswa.Kata Kunci: Reading, tipe STAD.